Evaluation of a Revised Home Medication Experience Questionnaire (HOME-Qv2) - Matthew J. Witry; Olajide O. Fadare; Kassi Pham (MDPI AG, 2020)
The Home Medication Experience Questionnaire (HOME-Qv2) was developed to identify patient medication experience issues for pharmacist intervention. The study objectives were to (1) evaluate patient responses to the HOME-Qv2 medication experience questionnaire and (2) describe recommendations made by pharmacists in response to the identified medication experience issues and adoption of recommendations. The study sample was comprised of older adults, 55 years and above, who have one or more chronic illnesses for which they routinely take 4+ prescription medications. The HOME-Qv2 was administered to patients and a pharmacist made recommendations based on the responses. At 3 months, the research team followed up with participants via telephone, during which the HOME-Qv2 was again administered and participants shared their adoption of recommendations. Twenty-four patients completed the questionnaire, and twenty-one were available for follow-up. At 3 months, there was a significant decrease in patient self-reported HOME-Qv2 medication experience issues. There were 31 interventions/recommendations provided by the pharmacists, and 64.5% reported adopted. The HOME-Qv2 appears to facilitate patient disclosure of medication experience issues and informed targeted pharmacist recommendations.